Owning the future: Why progressive politics in the 2020s must reject political short‐termism and find a new voice. Issue 1 (June 2016) - Kelly, Gavin; Pearce, Nick
Abstract : Gavin Kelly andNick Pearce argue that progressive politics must seek to understand long‐term social and economic trends and the electoral shifts that will come in their wake. Today's politicians mustn't let political short‐termism and the fallout from the Brexit crisis deflect them from the work of understanding how these forces will shape the politics of the 2020s.